1993
DOI: 10.1073/pnas.90.7.2633
|View full text |Cite
|
Sign up to set email alerts
|

Insulin receptor isotype expression correlates with risk of non-insulin-dependent diabetes.

Abstract: Skeletal muscle insulin resistance plays a pivotal role in the pathogenesis of non-insulin-dependent dia-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
1
1

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 28 publications
1
27
1
1
Order By: Relevance
“…Furthermore, this increase was positively correlated with plasma insulin concentration and negatively correlated with in vivo insulin sensitivity [58]. The results of this study may provide a key to the interpretation of the discordant data reported by the different studies [50][51][52][53][54][55]. In these latter reports, the metabolic state of the subjects studied ranged from glucose intolerance to overt diabetes and since this progression is usually paralleled by the decline in plasma insulin levels which accompany increases in glycemia, the differences in relative abundance of the two insulin receptor isoforms between normoglycemic and diabetic subjects may have been minimal or absent due to similar plasma insulin concentrations.…”
Section: Ir In Type 2 Diabetes 367mentioning
confidence: 51%
See 1 more Smart Citation
“…Furthermore, this increase was positively correlated with plasma insulin concentration and negatively correlated with in vivo insulin sensitivity [58]. The results of this study may provide a key to the interpretation of the discordant data reported by the different studies [50][51][52][53][54][55]. In these latter reports, the metabolic state of the subjects studied ranged from glucose intolerance to overt diabetes and since this progression is usually paralleled by the decline in plasma insulin levels which accompany increases in glycemia, the differences in relative abundance of the two insulin receptor isoforms between normoglycemic and diabetic subjects may have been minimal or absent due to similar plasma insulin concentrations.…”
Section: Ir In Type 2 Diabetes 367mentioning
confidence: 51%
“…Studies on the relative expression of the two mRNA transcripts have led to divergent observations [50][51][52][53][54][55]. Thus, three studies have reported that expression of the two mRNA species measured by polymerase chain reaction (PCR) is altered in skeletal muscle of both type 2 diabetic and pre-diabetic insulin-resistant subjects as compared to normal insulin-sensitive controls [50][51][52].…”
Section: Insulin Receptor Isoforms In Type 2 Diabetesmentioning
confidence: 99%
“…Studies on humans and animal models of insulin resistance have demonstrated defects in the insulin signalling cascade at levels as proximal as the insulin receptor expression level and its tyrosine kinase activity [48,49,50]. If insulin resistance is a result of such a proximal signalling defect, what is the physiological relevance of an additional breakage point further downstream, like the one described in this study ? We believe that the literature to date does not rule out a role for insulin signalling defect(s) downstream of PI 3-kinase.…”
Section: Discussionmentioning
confidence: 65%
“…It has been recently reported by some [22][23][24], but not all authors [16] that muscle tissue from insulin-resistant subjects (both diabetic and non-diabetic) has an increased proportion of the insulin receptor isoform exon 11+. This receptor isoform has a twofold lower affinity for the insulin molecule [25][26][27] and, consequently, a twofold lower sensitivity to insulin stimulation of its tyrosine-kinase activity [26,27], a decrease that is similar to the one we observed in the present study in muscle tissue of insulin-resistant subjects.…”
Section: Discussionmentioning
confidence: 97%